2022
DOI: 10.1002/adhm.202200011
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Polymer Hydrophilicity to Regulate Gel Mechanics and Encapsulated Cell Morphology

Abstract: Mechanically tunable hydrogels are attractive platforms for 3D cell culture, as hydrogel stiffness plays an important role in cell behavior. Traditionally, hydrogel stiffness has been controlled through altering either the polymer concentration or the stoichiometry between crosslinker reactive groups. Here, an alternative strategy based upon tuning the hydrophilicity of an elastin-like protein (ELP) is presented. ELPs undergo a phase transition that leads to protein aggregation at increasing temperatures. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…The CH vibrations were coherently driven by two laser beams overlapped in time and space, generated by a picosecond‐pulsed laser system consisting of a 1031 nm fiber laser and an optical parametric oscillator (OPO) tunable between 690–960 nm (APE picoEmerald S, 2 ps pulse length, 80 MHz repetition rate, and 10 cm −1 bandwidth). We have previously observed protein‐specific stretching modes of CH 3 for ELP in the range 2930–2940 cm −1 , and to address this vibration the OPO wavelength was set to 791 nm 11,18,22–25 . The CARS signal depends quadratically on the number density of the probed vibrational group, providing contrast for regions dense in ELP polymer without the need for external labels or other disruptive sample preparations.…”
Section: Methodsmentioning
confidence: 99%
“…The CH vibrations were coherently driven by two laser beams overlapped in time and space, generated by a picosecond‐pulsed laser system consisting of a 1031 nm fiber laser and an optical parametric oscillator (OPO) tunable between 690–960 nm (APE picoEmerald S, 2 ps pulse length, 80 MHz repetition rate, and 10 cm −1 bandwidth). We have previously observed protein‐specific stretching modes of CH 3 for ELP in the range 2930–2940 cm −1 , and to address this vibration the OPO wavelength was set to 791 nm 11,18,22–25 . The CARS signal depends quadratically on the number density of the probed vibrational group, providing contrast for regions dense in ELP polymer without the need for external labels or other disruptive sample preparations.…”
Section: Methodsmentioning
confidence: 99%
“…Development of materials conducive to directing cell behavior through local gene transfer in a spatiotemporally defined manner is critical to many tissue engineering and regenerative medicine applications. To achieve complex tissue organization and appropriate regrowth, attempts involve replicating key features of the extracellular matrix. , Gene delivery from extracellular matrix-like materials can then be used to direct cell fate . While the incorporation of a genetic material can be a powerful approach, its applicability is hampered by exonucleases which degrade them if they are unprotected in the extracellular space.…”
Section: Resultsmentioning
confidence: 99%
“…[44,45] Much of the literature has shown that global stiffness is able to modulate differentiation behavior. [10,46,47] However, bulk stiffness values are measured at a scale much larger than what cells are able to sense. In addition, local stiffness profiles do not necessarily correlate with global stiffness.…”
Section: Discussionmentioning
confidence: 99%